2015
DOI: 10.3892/etm.2015.2286
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells expressing interleukin-18 suppress breast cancer cells in vitro

Abstract: Breast cancer is the most common malignancy among females throughout the world. Current treatments have unsatisfactory outcomes due to the dispersed nature of certain types of the disease. The development of a more effective therapy for breast cancer has long been one of the most elusive goals of cancer gene therapy. In the present study, human mesenchymal stem cells derived from umbilical cord (hUMSCs) genetically modified with interleukin 18 (IL-18) gene were used to study the effect of hUMSCs/IL-18 on the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…Prior research suggested that co‐culture of UCMSCs and tumor cells in vitro had functions of apoptosis induction and proliferation inhibition of tumor cell. For example, UCMSCs exhibited the obvious inhibition effects on tumorous growth in the research of malignant tumors including hepatocarcinoma, pulmonary carcinoma, colon carcinoma, mammary cancer, melanoma, and hematological malignancy (Alshareeda et al, ; Chai, Bai, Li, Chen, & Zhang, ; Hendijani, Javanmard, Rafiee, & Sadeghi‐Aliabadi, ; Hendijani, Javanmard, & Sadeghi‐aliabadi, ; Kawabata et al, ; Liu et al, ; Wang, Li, Chen, & Yang, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research suggested that co‐culture of UCMSCs and tumor cells in vitro had functions of apoptosis induction and proliferation inhibition of tumor cell. For example, UCMSCs exhibited the obvious inhibition effects on tumorous growth in the research of malignant tumors including hepatocarcinoma, pulmonary carcinoma, colon carcinoma, mammary cancer, melanoma, and hematological malignancy (Alshareeda et al, ; Chai, Bai, Li, Chen, & Zhang, ; Hendijani, Javanmard, Rafiee, & Sadeghi‐Aliabadi, ; Hendijani, Javanmard, & Sadeghi‐aliabadi, ; Kawabata et al, ; Liu et al, ; Wang, Li, Chen, & Yang, ).…”
Section: Discussionmentioning
confidence: 99%
“…This provides a new way in treating ovary diseases (Kim et al, 2018). (Alshareeda et al, 2018;Chai, Bai, Li, Chen, & Zhang, 2018;Hendijani, Javanmard, Rafiee, & Sadeghi-Aliabadi, 2015;Kawabata et al, 2013;Liu et al, 2015;Wang, Li, Chen, & Yang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study demonstrated the safety and usability of hUCMSCs-LV-IL-21 in ovarian cancer gene therapy, suggesting the strategy may be a promising new method for clinical treatment of ovarian cancer (Zhang et al, 2014). In a very recent study, it was reported that hUCMSCs secreting IL-18 can suppress the proliferation, migration, and invasion of breast cancer cells in vitro and may provide an approach for a novel antitumor therapy in breast cancer (Liu et al, 2015). The results of these experiments indicate that stem cell-delivered ILs have the potential to be used as an alternative strategy for cancer therapy.…”
Section: Stem Cell -Cytokine Therapymentioning
confidence: 97%
“…Combined therapeutic modalities including surgery, chemotherapy, radiotherapy, endocrine and targeted therapies are the mainstay of treatment. However, they may lead to unsatisfactory outcomes, mainly due to the difficulty in accessing tumor sites, the dispersed nature of the disease and the toxicity of the treatment (Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%